The Effect of Educational Units According to the Cognitive Training Strategy on Cognitive Flexibility and Learning the Skill of Scoring in Football - Nashmi, Muneeb Hassan; Rashid, Abdul Rahman Nasser; Dhiyab, Adel Abbas (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The first chapter contained the introduction and importance of the research, as the importance of using the cognitive training strategy according to cognitive flexibility was addressed for learning football for first-stage students. The research aims to address whether educational units developed by the researchers positively influence learning outcomes in football scoring. The objectives of the research were to prepare educational units using a cognitive training strategy according to cognitive flexibility in learning the skill of scoring in football. Where the research areas were: The human field: first-year students in the College of Basic Education, Department of Physical Education and Sports Sciences / Al- Mustansiriya University, the time field: for the period from 10/12/2022 until 2/ 10/2023. As for the research community, it was represented by the students of the first stage in the College of Basic Education/Al- Mustansiriya University (70) students. The sample consisted of two equal groups (10), experimental and control. The Vina system was used using a three-dimensional test to determine cognitive flexibility. The researcher conducted pre-tests for the research sample, then the main experiment was applied for a period of 10 weeks, one educational unit per week, after which the researcher conducted the post-tests and the pre-tests with the same procedures, which indicated that there were significant differences between the two research groups and in favor of the experimental group. The conclusions were that there was a positive impact of the educational units used in the research to learn skills, as the researcher recommended using a cognitive training strategy according to cognitive flexibility in learning other skills.